2008
DOI: 10.1148/radiol.2473071097
|View full text |Cite
|
Sign up to set email alerts
|

Anterior and Posterior Cruciate Ligaments at Different Patient Ages: MR Imaging Findings

Abstract: During growth, angulation of the ACL is age dependent. The angle and morphologic changes of the PCL are age dependent throughout skeletal maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 14 publications
10
92
2
Order By: Relevance
“…[5] the diagnostic accuracy of acute knee injuries in younger patients is not as much as that in adults [9,10,11] .The expanded difficulty in correctly diagnosing acute knee injuries in kids has been proposed to be partly because the naturally more prominent laxity in the knees of children, [10] and the decreased sensitivity and specific city of magnetic resonance imaging (MRI)may likewise play a role. [9] Advances in imaging study and expanded the awareness of ACL injuries in this populace will probably enhance diagnostic accuracy later on [12] .The combination of injury history, clinical examination, and imaging specially MRi is recommended to optimize the diagnostic accuracy of ACL injuries in skeletally immature people [11,13] .…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…[5] the diagnostic accuracy of acute knee injuries in younger patients is not as much as that in adults [9,10,11] .The expanded difficulty in correctly diagnosing acute knee injuries in kids has been proposed to be partly because the naturally more prominent laxity in the knees of children, [10] and the decreased sensitivity and specific city of magnetic resonance imaging (MRI)may likewise play a role. [9] Advances in imaging study and expanded the awareness of ACL injuries in this populace will probably enhance diagnostic accuracy later on [12] .The combination of injury history, clinical examination, and imaging specially MRi is recommended to optimize the diagnostic accuracy of ACL injuries in skeletally immature people [11,13] .…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Less experience with interpretation of pediatric knee MRI contributes to the difficulty making accurate diagnoses as does the high incidence of partial injuries and the changes in morphology with age. For example, Kim et al [22] demonstrated an increase of the angle between the ACL and the tibial plateau in both the coronal and sagittal planes as the child matures. Classic MRI findings of discontinuity of ACL fibers and lateral compartment bone contusions may not be as reliable in the pediatric population as in the adult population [23,24].…”
Section: Imagingmentioning
confidence: 99%
“…Recently, the pediatric literature has particularly focused on MRI characteristics of the ACL and the epiphyseal dimensions [18][19][20][21]. These studies have aimed to further characterize pediatric knee anatomy to determine optimal surgical candidates and techniques for safe ACL reconstruction in skeletally immature patients.…”
Section: Acl and Physeal Anatomymentioning
confidence: 99%